Toxicity of Silver Nanoparticles at the Air-Liquid Interface. (24th December 2012) - Holder, Amara L.; Marr, Linsey C.
Abstract : Silver nanoparticles are one of the most prevalent nanomaterials in consumer products. Some of these products are likely to be aerosolized, making silver nanoparticles a high priority for inhalation toxicity assessment. To study the inhalation toxicity of silver nanoparticles, we have exposed cultured lung cells to them at the air-liquid interface. Cells were exposed to suspensions of silver or nickel oxide (positive control) nanoparticles at concentrations of 2.6, 6.6, and 13.2 μ g cm −2 (volume concentrations of 10, 25, and 50 μ g ml −1 ) and to 0.7 μ g cm −2 silver or 2.1 μ g cm −2 nickel oxide aerosol at the air-liquid interface. Unlike a number of in vitro studies employing suspensions of silver nanoparticles, which have shown strong toxic effects, both suspensions and aerosolized nanoparticles caused negligible cytotoxicity and only a mild inflammatory response, in agreement with animal exposures. Additionally, we have developed a novel method using a differential mobility analyzer to select aerosolized nanoparticles of a single diameter to assess the size-dependent toxicity of silver nanoparticles.